Knowledge, Attitudes, and Practices Toward Hepatitis B Virus Among Medical Students and Residents in Northwest Libya - Ali Madour; Rahmah Aboulqasim; Rahma Alkurdi; Hana Alaswad; Amani Jafaari; Ehab Naji; Eanas Elmaihub (African Journal of Advanced Pure and Applied Sciences, 2025)
Background: Hepatitis B remains a major global public health concern and poses a significant threat to human health. In Libya, particularly in the northwest region, there is limited evidence on the knowledge, attitudes, and practices (KAP) of the general population and medical students toward hepatitis B virus (HBV) infection. Understanding baseline knowledge is essential for both the public and healthcare trainees to guide prevention strategies. Furthermore, the attitudes of future physicians play a pivotal role in controlling disease transmission and shaping patient care. Objective: This study aimed to evaluate the KAP regarding HBV among residents and medical students in northwest Libya. Methods: A cross-sectional descriptive survey was conducted among 1,000 residents and 70 dental students in northwest Libya. Data were collected through a questionnaire administered both electronically and face-to-face. The survey assessed knowledge of HBV infection, transmission routes, vaccination, and participants’ attitudes and practices toward HBV patients. Data were analyzed using SPSS version 23, with statistical significance set at p < 0.05. Results: The majority of residents demonstrated poor knowledge regarding HBV infection, while medical students showed only basic awareness of the disease. Despite this, participants exhibited generally positive attitudes toward prevention, and reported practices reflected an effort to protect themselves from infection. Conclusion: Knowledge of HBV was insufficient among residents and limited among medical students, although preventive attitudes and practices were reported. Public health campaigns are urgently needed to raise awareness about HBV and its prevention. Additionally, targeted educational interventions for medical students are essential to foster supportive attitudes, reduce stigma, and improve the quality of care for individuals living with HBV.